Study on Factors Affecting Power Generation Efficiency of Microbial Fuel Cells - Chen Zitao (MATEC Web of Conferences)
This article studies the application of microbial fuel cells (MFCs) in scenarios involving the conversion of organic waste into renewable electrical energy. MFCs are aided by the electroactive bacteria, which oxidize the anode substrates at the cathode. This transfer of electrons from the anode to the cathode also results in wastewater treatment. The article presents a comprehensive review on the theoretical basis, most important parts of MFCs, and working principles. It emphasizes the influence of the choice of the substrate, the concentration, the microbial community composition, and the pH and temperature on the efficiency of MFC power generation. Furthermore, it discusses the problem in scaling microbial fuel cells due, in part, to expensive materials and the challenge of consistent microbial performance. Recent improvements like designing new biocatalysts or adopting microbial solar cells are analyzed as the most promising directions to accelerate the project's exploration of electron transfer rates and earning overall effectiveness. The study confirms the MFCs' potential as a practice for efficient waste management and familiar for powering; however, it recommends further research to perfect the MFC design and operations for pragmatic use.